(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Lubricating oils in nuclear power plants may contaminate with radionuclides and become a challenging radwaste for treatment because they decompose in storage and disposal. In addition, conventional methods of immobilization in cement should be checked. This work intends to compare cement and geopolymer used to solidify lubricating oil previously decontaminate using bentonite as sorbent material. Cement is a well-known matrix for radwaste immobilization and geopolymer (alkali-activated material) has been proposed as a new immobilization technology, due to its advantages comparing to cement and bitumen. The geopolymers are cementitious binders formed by aluminosilicates activated in alkaline medium. Synthesis occurs by means of polymerization or polycondensation reactions from the dissolution of SiO44- and AlO45- ions of the aluminosilicates in a highly alkaline solution. After the treatment of the oil radwaste, the contaminated bentonite was immobilized in geopolymer and cement matrix and the final immobilized waste properties were evaluated: compressive strength and homogeneity. The compressive strength result in cement matrix specimens (13,38 MPa) has been higher than in geopolymer matrix (5,96 MPa). Nevertheless, when the homogeneity was compared, the resultant waste in geopolymer presented an aspect more homogeneous than the in the cement matrix. The results showed that the contaminated bentonite was not distributed homogeneously in cement matrix, for this reason the cement was not adequate to solidify the simulated waste. The compressive strength result for the waste in geopolymer matrix did not meet the Brazilian waste acceptance criteria. Therefore, new compositions of geopolymer matrix using less water will be carried out to improve the compressive strength and reach the recommended by Brazilian legislations.